Pairing with strings attached - Gärttner, Martin; Garst, Markus (Nature physics, 2022)
Charge carriers in an engineered bilayer Mott insulator are predicted to form tightly bound, mobile pairs, glued together by string excitations of the antiferromagnetic order — a scenario that can be tested with quantum gas microscopy experiments.